Differential Roles of the Two Raphe Nuclei in Amiable Social Behavior and Aggression – An Optogenetic Study - Balázsfi, Diána; Zelena, Dóra; Demeter, Kornél; Miskolczi, Christina; Varga, Zoltán K.; Nagyváradi, Ádám; Nyíri, Gábor; Cserép, Csaba; Baranyi, Mária; Sperlágh, Beáta; Haller, József (Frontiers in Behavioral Neuroscience, 2018)
Serotonergic mechanisms hosted by raphe nuclei have important roles in affiliative and agonistic behaviours but the separate roles of the two nuclei are poorly understood. Here we studied the roles of the dorsal (DR) and median raphe region (MRR) in aggression by optogenetically stimulating the two nuclei. Mice received three 3 min-long stimulations, which were separated by non-stimulation periods of 3 min. The stimulation of the MRR decreased aggression in a phasic-like manner. Effects were rapidly expressed during stimulations, and vanished similarly fast when stimulations were halted. No carryover effects were observed in the subsequent three trials performed at two-day intervals. No effects on social behaviours were observed. By contrast, DR stimulation rapidly and tonically promoted social behaviours: effects were present during both the stimulation and non-stimulation periods of intermittent stimulations. Aggressive behaviours were marginally diminished by acute DR stimulations, but repeated stimulations administered over 8 days considerably decreased aggression even in the absence of concurrent stimulations, indicating the emergence of carryover effects. No such effects were observed in the case of social behaviours. We also investigated stimulation-induced neurotransmitter release in the prefrontal cortex, a major site of aggression control. MRR stimulation rapidly but transiently increased serotonin release, and induced a lasting increase in glutamate levels. DR stimulation had no effect on glutamate, but elicited a lasting increase of serotonin release. Prefrontal serotonin levels remained elevated for at least two hours subsequent to DR stimulations. The stimulation of both nuclei increased GABA release rapidly and transiently. Thus, differential behavioural effects of the two raphe nuclei were associated with differences in their neurotransmission profiles. These findings reveal a surprisingly strong task division between the two raphe nuclei and also suggest that serotonergic and non-serotonergic raphe mechanisms interactively control aggression.